1997
DOI: 10.3109/10715769709097863
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Improves the Aminotransferase Status of Patients Suffering from Viral Hepatitis C: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: pro-spective randomized double-blind crossover design. Clinical parameters including alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were determined for monitoring the disease state, in parallel vitamin E plasma levels and plasma lipids were determined. The plasma levels of the alpha-tocopherol were increased about 2-fold in all 23 patients. In 11 of 23 patients the clinical parameters indicative of liver damage were improved during the phase of vitamin E treatment (48% responders). ALT lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 10 publications
0
49
0
Order By: Relevance
“…In cells, vitamin E is the major lipid soluble chain-breaking antioxidant in mitochondria, microsomes, and lipoproteins [46] . von Herbay et al [47] reported that vitamin E decreases the hepatic aminotransferase levels in patients whit chronic HCV infection. Murakami et al [48] observed that antioxidant vitamins (E and C) supplemented during interferon alpha treatment inhibited the decrease in eicosapentaenoic acid of mononuclear cell.…”
Section: Vitamins C and Ementioning
confidence: 99%
See 1 more Smart Citation
“…In cells, vitamin E is the major lipid soluble chain-breaking antioxidant in mitochondria, microsomes, and lipoproteins [46] . von Herbay et al [47] reported that vitamin E decreases the hepatic aminotransferase levels in patients whit chronic HCV infection. Murakami et al [48] observed that antioxidant vitamins (E and C) supplemented during interferon alpha treatment inhibited the decrease in eicosapentaenoic acid of mononuclear cell.…”
Section: Vitamins C and Ementioning
confidence: 99%
“…Based on the multiple oxidant and antioxidant activities performed in vivo and in vitro systems during viral infections, and the variable ability of antioxidants to cross cell membranes, the systematic use of antioxidants as antiviral therapies had been limited [40] . On the other hand, HCV is potentially lymphotropic, because it can invade and propagate in cells of the [47,48] 400-544 IU/d or 600 mg 1 Vitamin C [48] 500 mg-10 g N-acetylcysteine [78] 600 mg or 1800 mg/d 1 Mitoquine Q [65,66] 40 or 80 mg/d 伪-tocopherol [79] 600 mg, 500 mg/d, 800 IU/d Glycyrrhizin [40,42,53,54] 500 mg, 120 mg Different mechanisms Silymarin (Silibinin A, Silibinin B, etc.) [40,64,[80][81][82] 250 mg or 5-20 mg/kg 1 S-adenosylmethionine [69] 1600 mg/d 1 Acetylsalicylic acid [73] 4 mmol/L (in vitro) Gallic acid 300 mg/mL (in vitro) 1 Combined treatment with interferon.…”
Section: Antioxidant Therapymentioning
confidence: 99%
“…On the other hand, it has also been reported that a-tocopherol failed in preventing hepatocellular carcinoma in patients with liver cirrhosis and positive history of HCV infection (Takagi et al, 2003). Moreover, Kugelmas et al (2003) demonstrated that supplementation with 800 IU vitamin E daily dose for 12 weeks in overweight non-alcoholic steatohepatitis patients did not cause statistically significant improvement in liver enzyme levels beyond weight loss alone (Von Herbay et al, 1997).…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, many therapeutic intervention with antioxidant compounds have been proposed (Loguercio et al, 1996;Peterhans, 1997;Jones and Czaja, 1998;Jakus and Lopuchova, 1999;Kaplowitz, 2000;Mori and Hirayama, 2000;Par et al, 2000;Schlenker et al, 2000). Extracts from Sylibum marianum, Salvia milthiorriza, Psyllantus amarum and glutathione, S-adenosylmethionine, sylimarin, vitamin E, Nacetyl-cysteine, ursodeoxycholic acid have been proposed in the treatment of viral and alcoholic liver diseases (Houglum et al, 1997;Ott et al, 1997;Von Herbay et al, 1997;Flora et al, 1998;Kaiano et al, 1998;Pares et al, 1998;Wasser et al, 1998;Mato et al, 1999;Mitsuyoshi et al, 1999;Shuppan et al, 1999) in combination with the pharmacological treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Herbay et al [49] treated 23 chronic hepatitis C patients refractory to interferon therapy with high doses of vitamin E (2 x 400 IU a-tocopherol/d) for 12 wk. In 11 of these patients, ALT and AST levels improved during treatment.…”
Section: Vitamin E (A-tocopherol)mentioning
confidence: 99%